2018
DOI: 10.1111/clr.13133
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐conditioned medium modulates the osteoconductive properties of collagen membranes in a rat calvaria defect model

Abstract: These results demonstrate that the commercial collagen membrane holds an osteoconductive competence in a rat calvaria defect model. Soaking collagen membranes with BCM shifts bone formation toward the formation of bony islands rather than new bone connected to the host bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 31 publications
12
41
0
Order By: Relevance
“…Previous immunohistochemical observations suggested that collagen membranes participate in the bone regenerative process, as indicated by the positive immunoreactivity for bone proteins (ALP, OP and OC) within the lower side of the membrane that interfaces with the underlying tibia bone defect (Figure ; Taguchi et al., ). The immunohistochemical observations are corroborated by recent histological and electron microscopy findings showing bone formation and mineralization within the lower porous part of a similar collagen membrane, covering calvarial bone defect, after 4 weeks of healing (Kuchler et al., ). Recently, the emerging hypothesis of a bioactive role of the GBR membrane has been addressed in vivo with a collagen membrane derived from the porcine small intestinal submucosa (Turri et al., ).…”
Section: Results Of the Literature Surveysupporting
confidence: 71%
“…Previous immunohistochemical observations suggested that collagen membranes participate in the bone regenerative process, as indicated by the positive immunoreactivity for bone proteins (ALP, OP and OC) within the lower side of the membrane that interfaces with the underlying tibia bone defect (Figure ; Taguchi et al., ). The immunohistochemical observations are corroborated by recent histological and electron microscopy findings showing bone formation and mineralization within the lower porous part of a similar collagen membrane, covering calvarial bone defect, after 4 weeks of healing (Kuchler et al., ). Recently, the emerging hypothesis of a bioactive role of the GBR membrane has been addressed in vivo with a collagen membrane derived from the porcine small intestinal submucosa (Turri et al., ).…”
Section: Results Of the Literature Surveysupporting
confidence: 71%
“…In support for the latter concept are our findings that ABL considerably reduced osteogenic differentiation of calvaria cells, similar to TGF-β 44 and bone BCM 17 in MC3T3E1. Moreover, BCM loaded onto a collagen membrane can reduce bone formation in rat calvaria defects 45 . Thus, the clinical relevance of the present data has to be interpreted with caution, particularly with respect to the role of TGF-β1 released from bone grafts during graft consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the most strongly regulated genes in oral fibroblasts are the consequence of TGF-β signalling, the possible cellular response to other growth factors and bioactive molecules within the ABL remain to be discovered. Another interesting approach would be to perform bone transplantation using mouse models with an osteoblast-specific TGF-β knock out 50 . This research can provide the scientific basis to refine protocols aiming to maintain growth factors and their activity during the preparation of allografts.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedures were performed as previously described (Kuchler et al, 2018). Briefly, all rats received ketamine (50 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Since TGF‐β adsorbs to collagen (Hempel et al, 2012) and thus to the classical collagen barrier membranes (Stahli et al, 2016), these membranes can be considered as suitable carriers to investigate ABLs on bone regeneration in vivo. Using this approach, we recently demonstrated that bone‐conditioned medium lyophilized onto collagen membranes slightly reduces bone formation in rat calvaria defects (Kuchler et al, 2018). Taking advantage of this established model, the aim of the present study was, therefore, to examine the impact of ABL adsorbed to collagen membranes on bone regeneration in rat calvaria defects.…”
Section: Introductionmentioning
confidence: 99%